FACTORS IN BLEEDING FROM GASTRIC AND DUODENAL ULCERS. - Makhmanazarov O.M.,; Khusenov I.Kh., (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Summary. Currently, bleeding due to gastric and duodenal ulcers has doubled, especially in the elderly and the elderly. The mortality rate from acute bleeding from ulcers in the gastrointestinal tract is 5-20%, while after emergency operations it is 4-73%, and in the elderly this figure is more than 80%.